2015
DOI: 10.1128/jcm.01806-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the RealTime HIV-1, Xpert HIV-1, and Aptima HIV-1 Quant Dx Assays in Comparison to the NucliSens EasyQ HIV-1 v2.0 Assay for Quantification of HIV-1 Viral Load

Abstract: , and good agreement were observed among all assays, although the Xpert and Aptima assays, which provided the most similar outputs (estimated mean viral loads of 2.67 log copies/ml [95% confidence interval [CI], 2.50 to 2.84 log copies/ml] and 2.68 log copies/ml [95% CI, 2.49 to 2.86 log copies/ml], respectively), correlated best with the RealTime assay (89.8% concordance, with Pearson r values of 0.97 to 0.98). These three assays exhibited greater precision than the NucliSens v2.0 assay. All assays were equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 23 publications
(25 reference statements)
9
42
0
Order By: Relevance
“…We observed a slight overestimation of viral load by the Xpert HIV-1 viral load assay, which is consistent with other studies (21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed a slight overestimation of viral load by the Xpert HIV-1 viral load assay, which is consistent with other studies (21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
“…Despite the development of several POC viral load technologies over the last decade (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), there is a shortage of commercially available tests. In this study, we evaluated the performance of the POC Cepheid Xpert HIV-1 viral load test in rural communities in Botswana in order to provide additional data to policy makers regarding the use of this assay in decentralized HIV treatment programs.…”
mentioning
confidence: 99%
“…Thus, differences in quantitation between the three assays can be normalized to nearly equivalent levels if the data are expressed in international units, although quantitation of subtypes C, F, and G and CRF02_AG would still be 0.20 to 0.25 log lower by RealTime assay than by Aptima assay. Overall differences in quantitation among the three assays are relatively small and are comparable across diverse group M subtypes, recombinant circulating forms, and group O samples, and the results are consistent with previous studies (30)(31)(32)(33)(34)(35)(36). Our study demonstrates the excellent linearity and accuracy of the Aptima assay in quantifying viral load measurements on diverse HIV-1 subtypes, groups, and circulating recombinant forms, even at very low RNA levels.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies on the performance of quantitative assays carried out on limited numbers of HIV-1 subtypes showed significant variability between viral load assays on different subtypes. Underquantitation of subtype A1 samples by the NucliSens v2.0 and RealTime assays, of subtype C by the RealTime assay, and of subtypes G and CRF02_AG by the NucliSens EasyQ v2.0 test was observed relative to the Xpert and Aptima assays, particularly for samples in the lower viremic range (35). Similarly, subtype CRF02_AG was underestimated by the NucliSens EasyQ v2.0 test (36), while the Aptima assay showed greater sensitivity than the CAP/CTM or RealTime assay on viral isolates and clinical samples but equivalent quantification on clinical samples and isolates belonging to HIV groups M, N, O, and P (34).…”
Section: Discussionmentioning
confidence: 97%
“…While several studies have compared Aptima to a variety of HIV-1 virus load tests (25,26,(32)(33)(34)(35), to date, only the studies from Hopkins et al (25) and Nair et al (26) have compared Aptima with CAP/CTM. Consistent with the evaluation presented here, in those studies linearity was confirmed using commercially available material, similar levels of precision were observed at low virus loads, and there was good agreement between methods for both qualitative and quantitative results.…”
Section: Discussionmentioning
confidence: 99%